Rebamipide suppresses TNF‐α production and macrophage infiltration in the conjunctiva. (18th December 2017) - Tajima, Kazuki; Hattori, Takaaki; Takahashi, Hiroki; Katahira, Haruki; Narimatsu, Akitomo; Kumakura, Shigeto; Goto, Hiroshi
Abstract: Purpose: To evaluate the anti‐inflammatory effect of rebamipide during corneal epithelial wound healing using a mouse wound repair model. Methods: A 2‐mm circular disc of the central cornea was demarcated in the right eye of C57BL/6 mice and the epithelium removed. Rebamipide 2% eyedrop was instilled onto the wounded eye 5 times a day ( n = 26). Phosphate‐buffered saline (PBS) was used in the control group ( n = 26). Corneal and conjunctival IL‐1β and TNF‐α levels were measured at 6 h and 24 h postinjury by ELISA. The wounded area was evaluated by fluorescein staining at 24 h postinjury. Macrophage infiltration was assessed immunohistochemically, and TNF‐α secretion from macrophages was examined in vitro . Results: Conjunctival IL‐1β and corneal IL‐1β levels were not significantly different between PBS‐treated and rebamipide‐treated groups. However, conjunctival TNF‐α level was significantly lower in the rebamipide‐treated group compared with the PBS‐treated group. Macrophage migration into the conjunctiva, but not into the cornea, was suppressed by rebamipide treatment. In addition, TNF‐α secretion from cultured macrophages was suppressed by rebamipide in a concentration‐dependent manner. Rebamipide treatment significantly accelerated corneal epithelial wound healing at 24 h postinjury. Conclusions: In a mouse corneal epithelial wound model, rebamipide suppressed TNF‐α secretion and macrophage infiltration in the conjunctiva, which might have contributed to accelerated corneal epithelial wound healing in the first 24 h following injury.